2013
DOI: 10.5606/tjr.2013.3269
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Pack-Years of Smoking and Disease Activity, Quality of Life, Spinal Mobility, and Sacroiliitis Grading in Patients with Ankylosing Spondylitis

Abstract: Amaç: Bu çalışmada İranlı ankilozan spondilit (AS) hastalarında sigara paket yılı ve hastalık aktivitesi, yaşam kalitesi, spinal mobilite ve sakroileit derecelendirmesi ve AS arasındaki ilişki araştırıldı. Sonuç: Bir grup İranlı AS hastasında sigara miktarı ve hastalık aktivitesi ve yaşam kalitesi arasında bağımsız bir ilişki olduğu doğrulandı. Ayrıca içilen sigara miktarı ve spinal mobilite arasında da bir ilişki vardı; ancak bu başka ilintili faktörlere bağlıydı. Sigara içen hastalara, daha iyi sonuçlar elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
5
8
1
Order By: Relevance
“…These findings are in agreement with three of the six existing studies of pack-years in AS [7, 8, 13]. Chen et al [8] reported unadjusted correlation between pack-years and BASFI, but not BASDAI, ESR or CRP.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are in agreement with three of the six existing studies of pack-years in AS [7, 8, 13]. Chen et al [8] reported unadjusted correlation between pack-years and BASFI, but not BASDAI, ESR or CRP.…”
Section: Discussionsupporting
confidence: 90%
“…Chen et al [8] reported unadjusted correlation between pack-years and BASFI, but not BASDAI, ESR or CRP. An Iranian study found pack-years to be associated with BASDAI and of quality of life (QoL) but not BASMI in cohort of very light current smokers (median of 0.6 pack-years) [13]. The largest and most robust study found associations between categories of pack-years and all of their markers including BASDAI, BASFI, pain numerical rating score and two measures of QoL [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Hazes, the most frequent range of age at onset of complaints was 50s years [7]. Similarly, in the study of Fallahi, the most frequent range of age at onset of complaints was 30s years in patients with AS [22]. The core key result of our study was that heavily smoking was associated with early onsets of AS and RA symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…When evaluated according to gender, 22.8% of women (n=18) and 69.7% of men (n=46) were smokers. Fallah et al [22] reported in their study that the smoking rate among patients with AS was 29.4%, while Hazes et al [7] reported the rate of smoking in patients with RA as 33.0%. Again, Hazes et al reported in their study that the alcohol consumption in patients with RA was 23.0%, while the rate in our study was only 7.6%.…”
Section: Discussionmentioning
confidence: 95%